2018
DOI: 10.1155/2018/6598326
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Cardiac Tissue of Patients Undergoing Coronary Artery Bypass Graft Surgery: The Effects of Overweight and Obesity

Abstract: Background Obesity is one of the major cardiovascular risk factors and is associated with oxidative stress and myocardial dysfunction. We hypothesized that obesity affects cardiac function and morbidity by causing alterations in enzymatic redox patterns. Methods Sixty-one patients undergoing coronary artery bypass grafting (CABG) were included in the study. Excessive right atrial myocardial tissue emerging from the operative connection to the extracorporeal circulation was harvested. Patients were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 109 publications
0
16
1
2
Order By: Relevance
“…These findings likely reflect a compensatory response to combat ROS elevation. Others have also reported increased antioxidant defences in obese hearts 57,58 .…”
Section: Discussionmentioning
confidence: 90%
“…These findings likely reflect a compensatory response to combat ROS elevation. Others have also reported increased antioxidant defences in obese hearts 57,58 .…”
Section: Discussionmentioning
confidence: 90%
“…Overweight and obesity are due to an imbalance between energy intake, storage, and expenditure including interactions with hereditary and environmental factors 2 4 . They result in numerous metabolic disorders such as dyslipidemia, non-alcoholic fatty liver, hyperglycemia, insulin resistance, and are characterized by chronic inflammation and oxidative stress 5 7 . These pathologies lead to many physiological disorders such as cardiovascular complications as well as the development of type 2 diabetes and contribute to increased morbidities 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In patients who have a BMI increase, suffer from CAD and will undergo CABG, increased ROS levels, increased expression of ROS-producing enzymes (P47phox, xanthine oxidase), decreased expression of antioxidant enzymes (mitochondrial aldehyde dehydrogenase, heme oxygenase-1, and eNOS), and increase in markers of inflammatory processes in serum and right atrial myocardial tissue (sVCAM-1 and CCL5/RANTES) have been demonstrated [ 115 ].…”
Section: Oxidative Stress In Coronary Artery Diseasementioning
confidence: 99%